Validação do questionário de avaliação da atividade física em crianças com idade entre 9 e 10 anos - Fernandes, Carolina Dadalto Rocha (2012)
Experiments with physical activity during childhood have an important influence on behavior during life, because at that stage there is increased susceptibility to behavioral changes and to adopt healthy lifestyle habits that tend to remain in adulthood. Although known the enormous contribution of physical activity on health, their study is not an easy task. Because it is an important variable in health research, it is essential to measuring and imperative in the context of epidemiological research, but the instrument used in these studies must be validated for use in specific population groups. The objective of this study was to test the validity of physical activity questionnaire of the SAUDES study, conducted with children of 9 and 10 years, resident in the metropolitan area of Vitória / ES. The sample consisted of 107 children whose mothers or guardians completed a questionnaire of physical activity of children. Children used the motion sensor pedometer (DW-701 SW) for three consecutive days, following guidance on its use. To compare both methods were performed Pearson correlation test and Kappa. Most children were male (55.1%), public school student (74.8%), normal weight (57%), social classes C and D (53.5%) and skin color is not white (80.4%). Considered active 50.5% and 88.8% of children, according to the methods of the pedometer and questionnaire, respectively. The Pearson correlation coefficient between the methods ranged from 0.20 to 0.27 (p <0.05). In the analysis of agreement was observed weighted kappa ranging from 0.17 to 0.28. Results showed poor correlation and reasonable degree of concordance between the variables of the questionnaire and the pedometer, but significant. Negative correlation was observed between screen time and number of steps obtained by the motion sensor. It was concluded that the questionnaire of the SAUDES study, here validated, can be used to assess physical activity in children, as presented on the ability to classify individuals into different levels of physical activity is recommended for use in population studies of children with characteristics like.